Increasing the popularity and efficiency of distance education by old-new methods - Pántya, Róbert; Mucsics F., László (Teaching Mathematics and Computer Science, 2010)
In our essay we aim to provide suggestions to develop distance education and we decisively focus on programmed education that is supported by e-learning environment. We both think that the shortage of programmed educational methods is causeless in Hungary’s distance education. The widespread usage of info-communication devices and of the Internet makes the programmed educational methods (not as an exclusive method) possible to use in distance education together with e-learning environment. In our work we summarize the possible solutions and at the same time we also provide a case study, as an insight into our e-learning project (called Logical Programming) by Moodle.